2014
DOI: 10.1083/jcb.201403138
|View full text |Cite
|
Sign up to set email alerts
|

HDAC4 integrates PTH and sympathetic signaling in osteoblasts

Abstract: During osteoclast differentiation, two extracellular cues that induce cAMP production both converge on HDAC4 and induce Rankl expression but do so using distinct signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 29 publications
(38 reference statements)
2
61
1
Order By: Relevance
“…Other studies using global HDAC 5 knock out mice demonstrated increased bone resorption with higher numbers of osteoclasts covering the bone surface due to significantly high levels of RANKL produced by osteoblasts [86]. Similar observations of high bone resorption and RANKL levels were also evident in mice with HDAC4 knocked out in osteoblasts suggesting a role for HDAC4 in the communications between osteoblasts and osteoclasts [86]. It is important to note in studies using HDAC global knockout mice that all bone cells would be affected making it difficult to determine the exact mechanisms of the changes in bone parameters.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…Other studies using global HDAC 5 knock out mice demonstrated increased bone resorption with higher numbers of osteoclasts covering the bone surface due to significantly high levels of RANKL produced by osteoblasts [86]. Similar observations of high bone resorption and RANKL levels were also evident in mice with HDAC4 knocked out in osteoblasts suggesting a role for HDAC4 in the communications between osteoblasts and osteoclasts [86]. It is important to note in studies using HDAC global knockout mice that all bone cells would be affected making it difficult to determine the exact mechanisms of the changes in bone parameters.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…For instance, in HDAC 5 global knock out mice there was an increase in sclerostin producing osteocytes with reductions in osteoblast number and defects in bone formation [74]. Other studies using global HDAC 5 knock out mice demonstrated increased bone resorption with higher numbers of osteoclasts covering the bone surface due to significantly high levels of RANKL produced by osteoblasts [86]. Similar observations of high bone resorption and RANKL levels were also evident in mice with HDAC4 knocked out in osteoblasts suggesting a role for HDAC4 in the communications between osteoblasts and osteoclasts [86].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Carfilzomib (CFZ), a next generation selective proteasome inhibitor, exhibits potent antimyeloma efficacy and decreased toxicity when compared with bortezomib and has been recently approved in the United States for the treatment of relapsed and refractory multiple myeloma (9). Both bortezomib and CFZ have been shown to directly inhibit osteoclast formation and bone resorption in vitro (10,11), and bortezomib was reported to inhibit PTH-induced Rankl mRNA expression in osteoblasts (12). However, how PTH and proteosomal inhibitors collectively regulate the complex interplay between osteoblasts and osteoclasts to in turn regulate bone resorption is poorly understood.…”
mentioning
confidence: 99%
“…HDAC4 accumulates in osteoblasts' nuclei , associates with ATF4 and is able to increase ATF4-dependent RANKL expression in osteoblasts following sympathetic stimulation [130]. In a recent work by Makinistoglu and Karsenty [131], HDAC4 has also been demonstrated to control Ocn expression, therefore working as an integrator of extracellular stimuli, such as sympathetic tone, that regulates Ocn expression.…”
Section: Other Bone-derived Hormonesmentioning
confidence: 99%
“…Recently, the role of the class II histone deacetylase 4 (HDAC4) has been investigated in the context of the osteoblasts [130]. HDAC4 accumulates in osteoblasts' nuclei , associates with ATF4 and is able to increase ATF4-dependent RANKL expression in osteoblasts following sympathetic stimulation [130].…”
Section: Other Bone-derived Hormonesmentioning
confidence: 99%